Eculizumab treatment for Chinese patients with hemolytic paroxysmal nocturnal hemoglobinuria (PNH): efficacy and safety – a single-center study - Leyu Wang; Ziwei Liu; Chen Yang; Miao Chen; Bing Han (Hematology)
Objective To evaluate the short-term efficacy and safety of eculizumab for the treatment of paroxysmal nocturnal hemoglobinuria (PNH) in China.Method Data were retrospectively collected from patients with PNH who received at least 3 months of full-dose eculizumab. Changes in clinical and laboratory indicators after 1, 3, and 6 months of eculizumab therapy and at the end of follow-up were documented. The incidence rates of breakthrough hemolysis (BTH), extravascular hemolysis (EVH), and adverse events were recorded.Result A total of 48 patients, including 27 males, with a median age of 46 (12–78) years were included. Twenty-four (50%) patients had classic PNH and 24 (50%) had bone marrow failure (BMF)/PNH. Eighteen (37.5%) patients required blood transfusion. The median duration of follow-up was 6 (3–15) months. During the follow-up period, Lactate Dehydrogenase (LDH) levels were lower than those at baseline (<0.05) at all observation points. The patients showed a significant reduction in creatinine levels from baseline (P = 0.022 and P = 0.039, respectively) at 1 and 3 months. At the end of the follow-up, fifteen (83.3%) became transfusion-independent. No new thrombotic events were observed. The FACIT-Fatigue score significantly improved (P < 0.05). No significant differences were observed in the changes in hemoglobin or LDH levels between patients with classic PNH and those with BMF/PNH. BTH was observed in 17.4% of patients and EVH in 10.4%. Mild adverse events occurred in 22.9% of patients. No deaths or clonal evolution was observed.Conclusion Eculizumab can effectively control the hemolytic symptoms of PNH with good tolerance for Chinese patients.